2016
DOI: 10.1016/j.biochi.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic endotoxemia with obesity: Is it real and is it relevant?

Abstract: Obesity is associated with metabolic derangements in multiple tissues, which contribute to the progression of insulin resistance and the metabolic syndrome. The underlying stimulus for these metabolic derangements in obesity are not fully elucidated, however recent evidence in rodents and humans suggests that systemic, low level elevations of gut derived endotoxin (lipopolysaccharide, LPS) may play an important role in obesity related, whole-body and tissue specific metabolic perturbations. LPS initiates a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
276
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(305 citation statements)
references
References 98 publications
10
276
0
19
Order By: Relevance
“…In adipose tissue, experimental endotoxin infusion in humans rapidly induces chemokine and T cell activation genes and therefore may potentiate leukocyte crosstalk and amplify initial inflammatory responses (105). This concept still remains somewhat controversial, as limitations in endotoxin measurement methods prevent the wide use of endotoxin as a true biomarker for metainflammation (106). However, the observation that treatment of obese adolescents leads to both improvements in insulin resistance and decreased endotoxin levels suggests that early interventions may limit metabolic endotoxemia (107).…”
Section: Resultsmentioning
confidence: 99%
“…In adipose tissue, experimental endotoxin infusion in humans rapidly induces chemokine and T cell activation genes and therefore may potentiate leukocyte crosstalk and amplify initial inflammatory responses (105). This concept still remains somewhat controversial, as limitations in endotoxin measurement methods prevent the wide use of endotoxin as a true biomarker for metainflammation (106). However, the observation that treatment of obese adolescents leads to both improvements in insulin resistance and decreased endotoxin levels suggests that early interventions may limit metabolic endotoxemia (107).…”
Section: Resultsmentioning
confidence: 99%
“…LPS-treated Bv.2 cells induced a pro-inflammatory response that was reduced by co-treatment with M2 cytokines or the sp 2 -iminosugar derivative R-DS-ONJ We stimulated Bv.2 cells, a mouse microglia cell line, with LPS (M1 stimulus) in the absence or presence of M2 cytokines (IL4/IL13). LPS was used as a pro-inflammatory stimulus since it induces an environment similar to that found in the obesity-related diabetic context [29]. Based on that, Bv.2 cells were cultured in the presence of LPS, IL4/IL13 (M2) and the combination of both (LPS + M2).…”
Section: Distribution Of Total Microglia (Resting and Activated) In Rmentioning
confidence: 99%
“…Low level elevations of gut derived endotoxin (lipopolysaccharide (LPS)) have been shown to play an important role in obesity [35], similarly to the consequential production of proinflammatory cytokines (such as interleukin-6 and tumor necrosis α (TNFα)) [36], resulting from LPS-induced TLR4 activation. Previous studies have shown that LPS, mimicking inflammation occurring during obesity, can affect the expression of several aquaglyceroporins.…”
Section: Introductionmentioning
confidence: 99%